Analysis of the stability of Zhangjiapo landslide. Issue 1 (October 2021) - Hou, Qian; Liu, Lixin; Chong, Jinxin; Li, Xueping
Abstract: The Zhangjiapo landslide in Xinling Town; Badong County has obvious deformation and a great hidden danger of safety in the past two years. In order to better treat the Zhangjiapo landslide, I quantify the stability of Zhangjiapo landslide using transfer coefficient method. And this method is compared and verified with the method of strength reduction stability analysis after using Rhino to establish geological model into FLAC3D. The results show that the stability coefficient is basically the same, and the Zhangjiapo landslide is extremely unstable under rainstorm condition. It proves the reliability of the paper's numerical simulation method in landslide research and provides a reference for the analysis of the landslide. According to the engineering geological characteristics of Zhangjiapo landslide and the influence of deformation area on landslide body, combined with the present situation of landslide, the comprehensive treatment scheme of landslide body "anti-slide pile+reinforcement of landslide front+drain" is put forward from the point of view of protecting environment.